A Promising Alternative for Treatment of Bacterial Infections by Sansevieria cylindrica Bojer ex Hook Leaf Extract - Buyun, Lyudmyla; Tkachenko, Halyna; Góralczyk, Anna; Maryniuk, Myroslava; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The aim of this study was to assess the in vitro antibacterial activity of ethanolic extract prepared from Sansevieria cylindrica Bojer ex Hook leaves against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa strains, clinically important bacteria, which are indicator organisms commonly used in programs to monitor antibiotic resistance. For this study, Staphylococcus aureus ATCC 25923, S. aureus ATCC 29213, S. aureus NCTC 12493, Escherichia coli ATCC 25922, E. coli ATCC 35218, Pseudomonas aeruginosa ATCC 27583 were used. The disc diffusion assay (Kirby–Bauer method) was used to screen for antibacterial activity of leaf extract. The results of antibacterial activity clearly showed that the extract has shown antibacterial activity against the entire tested organisms. The extract has shown better activity against S. aureus and P. aeruginosa strains compared to the E. coli strains. The diameters of inhibition zones were (22.5 ±1.24) mm, (20.5 ±1.3) mm, and (16.4 ±0.95) mm for S. aureus ATCC 25923, S. aureus ATCC 29213, and S. aureus NCTC 12493, respectively. The extract has shown less antimicrobial activities against P. aeruginosa. Finally, the ethanolic extract exhibited mild antibacterial activity against E. coli. Further chemical analysis of the aforementioned plant extract should be performed to determinate their chemical composition and identify the exact secondary metabolites responsible for the antimicrobial activity. In addition, the extract should be subjected to pharmacological evaluations with the aim of assessing its efficacy and toxicity, interactions and contraindications.